Foreign policy vision of the Turkish religious right: from national view to justice and development party - Hakan Koni, (Institut Kajian Rantau Asia Barat, 2011)
This article explores the transformation of the Turkish religious right in its view to the major goals and orientation of Turkish foreign policy from National View parties to the Justice and Development Party. The main argument of the paper is that foreign policy vision of Turkish religious right has shifted from a substantially cultural to a pragmatist and rational one. While the National View parties were opposed to develop relations with the West and were rather in favour of integration with the Muslim countries of the Middle East, the Justice and Development Party is motivated to integrate with the West and the East at the same time in search of achieving advanced political, economic and social institutions at home and in Turkey’s neighbourhood. It is a major goal of the Justice and Development Party to ensure Turkey’s membership to the EU which was formerly identified by the National View as a union of Christian states. The Justice and Development Party is also in cooperation with the USA in its goal to institute more democratic and peaceful regimes in the Middle East. While trying to promote contemporary political institutions in the Middle East, the Justice and Development Party is also in search of greater cooperation and partnership in economic,diplomatic and cultural terms. Behind this seemingly contradictory attitude lies the belief on the part of the Justice and Development Party deputies that democracy, human rights, rule of law, good governance are indisputable ideals of 21st century politics and that they are not in conflict with different cultural values enjoyed by the world community. The Justice and Development Party endeavours to make Turkey a centre country, a regional and global power, an advanced democracy and a respectable member of the international community.